The Effect of Drying Methods on the Chemical Composition of the Essential Oil of Caesalpinia Pulcherrima Growing in Lagos, Nigeria - Isaac S., Njoku; Olayinka T., Asekun; Oluwole I., Familoni (Covenant Journal of Physical and Life Sciences, 2017)
This research studied the effects of different drying methods on the yield and chemical composition of hydrodistilled essential oil from the red variety of leaves of Caesalpinia pulcherrima. A total of 26, 23, 30 and 25 compounds were identified in the oils of the fresh, air-dried, sun-dried and oven-dried plant materials, respectively. In general, the air-dried plant yielded more essential oils than the fresh, sun-dried and oven-dried plant. The air-dried, sun-dried and oven-dried plant materials yielded 0.90 %, 0.20 % and 0.58 % of the essential oils, respectively whereas the fresh plant materials yielded oils of 0.63 %. The essential oils of Caesalpinia pulcherrima were composed mainly of sesquiterpenoids. The fresh leaf oil comprises caryophyllene, 15.51 %; α -cadinol 14.36 %; γ–muurolene, 13.28 %; nerolidol 8.32 % as the most prominent components. While, the major components common to the different drying methods are air-dried; (phytol, 12.28%; copaene, 9.07 %; γ-pyronene, 8.95 %; neryl propanoate, 6.55 %), sun-dried (neryl propanoate, 8.18 %; copaene, 5.49 %; phytol, 4.72 %; γ -pyronene, 0.87 %), oven-dried (copaene, 18.77 %; neryl propanoate, 7.61 %; γ-pyronene, 4.59 %; phytol - 3.25 %). This results showed that similar major compounds were present in all the dried leaf oils but at varying quantities, whereas, they all differ from the major compounds of the fresh leaf oil. This disparity may be due to chemical transformation of the components in the different environ ments exposed to for moisture removal.